Mutation breeding in cultivar IAC-24 of wheat aiming at resistance to diseases - Neto, Augusto Tulmann; Camargo, Carlos Eduardo de Oliveira; Alves, Marcelo Correa; dos Santos, Rui Ribeiro; de Freitas, José Guilherme (Pesquisa Agropecuaria Brasileira, 1995)
The objective of the present work was to obtain mutants with disease resistance in the wheat cultivar IAC-24. Seeds were irradiated with gamma-rays (25 and 35 krad) and the selection was started in the M2 generation. Eight selected lines were compared with the control IAC-24 during three years (M6, M7 and M8 generations) in nine trials carried out in several locations with and without irrigation. Four mutant lines were immune to leaf rust and one of them showed also moderate resistance to powdery mildew. Another mutant line showed better reaction to leaf spot. Two of these mutant lines maintained the same yield, plant height and tolerance to aluminum toxicity as the control. These results show the usefulness of mutation breeding approach to correct defects in outstanding cultivars.